Teachers’ voices from the global south: Navigating chemical literacy through STEAM-PjBL in resource-limited Indonesian classrooms - Uyun, Farhatul; Suprihatiningrum, Jamil (American Journal of STEM Education, 2026)
This study examines how six chemistry teachers in Yogyakarta, Indonesia, implemented project-based STEAM learning to enhance chemical literacy and creativity within systemic constraints. Using a qualitative case study with semi- structured interviews analyzed thematically, teachers reported challenges such as limited time, inadequate laboratory facilities, uneven student readiness, and partial expertise in STEAM integration. They addressed these issues through virtual titrations, microscale buffer experiments, chemistry comics, natural indicators, and professional collaboration. Students demonstrated increased engagement, creativity, and critical reasoning, although macro–micro–symbolic translation remained difficult. The study introduces the R³ mechanism (Representations, Resources, and Rubrics) as vital for maintaining rigorous chemistry instruction in resource-limited environments, emphasizing both teacher agency and structural support.